The Impact of Audit Activity and Internal Control Effectiveness on Public Finance Management in Gambia - Jatta, Burama; Belford, Christopher; Badjie, Gibriel (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study addresses the impact of audit activity and internal control effectiveness on public finance management in The Gambia. Utilising empirical studies and theoretical frameworks, the study delves into the intricate dynamics of financial governance. Design/Methode/Approach: The study used the purposive sampling method for its specificity, allowing the selection of relevant and valuable respondents. This approach acknowledges that certain individuals or groups possess the information required by the study and, thus, choose its respondents to provide the needed data. Research Finding: The study highlights the crucial role played by robust internal controls and effective audit practices in fostering financial transparency, accountability, and efficiency. The findings underscore specific challenges, including management's limited commitment to implementing audit recommendations. Theoretical contribution/Originality: This study makes a noteworthy contribution by validating theoretical frameworks, specifically Agency, Control, and Resource Dependency theories. The empirical findings align with these theories, showcases their applicability to the dynamics of public finance management in The Gambia. This validation enhances the theoretical understanding of how audit activities and internal controls operate within the context of a developing country like the Gambia. Practitionel/Policy implication: To enhance financial governance, the study recommends updating the Public Finance Act, developing a policy for audit recommendation implementation, empowering internal audit units, and establishing an investigative institution. Research limitation: The small sample size constraints may introduce potential biases, and the perspectives expressed may not fully represent the diversity of viewpoints in Gambia's public finance management and lack generalization potentials.